Poor neurological sequelae of herpes simplex virus encephalitis in an infant despite adequate antiviral and adjunct corticosteroid therapy - Ratna B Basak; Varsha Malpani; Khalid Kakish; Susan Vargese; Nageshwar Chauhan; Andreas Boeck (Wolters Kluwer Medknow Publications, 2011)
A 2-month-old infant presented to our emergency department with fever, altered consciousness, and focal seizures of acute onset. He had vesicular skin lesions over the right preauricular region. CT brain showed a large hypodense lesion involving the left temporo-parietal region, left basal ganglia and left thalamus. MRI brain revealed bilateral multifocal corticomedullary lesions suggestive of encephalitis. CSF-PCR was positive for herpes simplex virus (HSV) type I. He was treated with standard dose intravenous acyclovir for 15 days along with a trial of pulse methylprednisolone, but was readmitted within a week with features of an early relapse. The infant survived but developed significant neurological sequelae. Although treatment of HSV is available, the neurological outcome is guarded even with adequate antiviral therapy. Adjunct corticosteroid therapy did not appear to attenuate the neurological sequelae.